Thrombolytic and Haemorrhagic Effects of Bolus Doses of Tissue-Type Plasminogen Activator and a Hybrid Plasminogen Activator with Prolonged Plasma Half-Life (K2tu-PA: CGP 42935) - Agnelli, Giancarlo; Pascucci, Claudia; Nenci, Giuseppe G; Mele, Antonio; Bürgi, Rolf; Heim, Jutta (Thrombosis and Haemostasis, 1993)
K2tu-PA is a hybrid plasminogen activator linking the kringle 2 domain of tissue-type plasminogen activator (t-PA) to the catalytic protease domain of single-chain urokinase-type plasminogen activator (scu-PA). K2tu-PA, as t-PA has high affinity for fibrin and is activated by fibrin but has a longer plasma half-life (over 30 min). The aim of this study was to compare the effects of bolus doses of recombinant t-PA (rt-PA) and K2tu-PA, on: 1) lysis of preformed thrombi (fibrinolysis), 2) accretion of new fibrin on pre-existing thrombi during fibrinolysis (thrombus growth), 3) thrombolysis as assessed by reduction of thrombus weight and 4) systemic plasma proteolysis and blood loss from a standard wound. A jugular vein thrombosis model and an ear bleeding model were adopted in rabbits. Saline produced 11 ± 2% fibrinolysis. rt-PA, 0.2 mg/kg, 0.4 mg and 0.8 mg/kg produced 35 ± 4%, 54 ± 4% and 78 ± 6% fibrinolysis, respectively. K2tu-PA, at the same doses, produced 39 ± 5%, 57 ± 6% and 83 ± 6% fibrinolysis, respectively. Thus, no differences in the fibrinolytic activity of rt-PA and K2tu-PA were observed. Injection of saline was followed by an accretion of 56.4 ± 5.9 μg of radioactive new fibrin on the thrombi. The injection of the three increasing doses of rt-PA was followed by an accretion of 54.9 ± 5.3 μg, 49.1 ± 6.1 μg and 47.2 ± 4.8 μg. The injection of three increasing doses of K2tu-PA was followed by an accretion of 38.1 ± 3.4 μg, 29.6 ± 2.5 μg and 17.1 ± 3.4 μg. At each of the three doses, K2tu-PA was more effective than rt-PA in reducing the accretion of new fibrin on the thrombi (p <0.01) and, as a consequence, in reducing thrombus weight (p <0.01). The two lower doses of rt-PA and K2tu-PA did not produce systemic proteolysis and bleeding. The highest dose of K2tu-PA produced a statistically significant more intense systemic proteolysis and bleeding than the highest dose of rt-PA.This study demonstrates that bolus doses of K2tu-PA and rt-PA produce a similar degree of fibrinolysis. Due to its longer half-life K2tu-PA is more efficient than rt-PA in inhibiting accretion of new fibrin on the thrombi during thrombolysis so that the thrombus size is more efficiently reduced. As a consequence the concomitant use of heparin might not be necessary. The potential increased risk of bleeding with bolus of high doses of K2tu-PA has to be seen in view of the advantage of avoiding the concomitant use of heparin.